2005
DOI: 10.2169/internalmedicine.44.1027
|View full text |Cite
|
Sign up to set email alerts
|

New Classification and Treatment for Myotonic Disorders

Abstract: Myotonia is repetitive firing of muscle action potentials causing prolonged muscle contractions even after mechanical stimulations to the muscles have ceased. Most common myotonic disorder is myotonic dystrophy which is now termed DM1, myotonic dystrophy type 1. In Japan, proximal myotonic myopathy, which is now called DM2 has not been reported. Both DM1 and DM2 have Cl channel abnormality which causes myotonia. Less commonly we encounter Thomsen's disease, and autosomal recessive generalized myotonia (Becker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
8
0
4
Order By: Relevance
“…Previous studies have indicated that membrane-depressant drugs, including phenytoin sodium and carbamazepine, may alleviate the symptoms of myotonia by promoting the activity of sodium pumps, leading to a reduction in intramembranous sodium concentration and an increase in resting membrane potential (30,31). In addition, physical training may aid the maintenance of normal muscle functions (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that membrane-depressant drugs, including phenytoin sodium and carbamazepine, may alleviate the symptoms of myotonia by promoting the activity of sodium pumps, leading to a reduction in intramembranous sodium concentration and an increase in resting membrane potential (30,31). In addition, physical training may aid the maintenance of normal muscle functions (22).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the limitations on this study, first of all, this was a singlecenter, retrospective study, and bias could be inherent in this type Second, this study included many types of NMDs. For example, although it is known that myotonic dystrophy involves channel abnormalities and develops into arrhythmias, 21 this pathogenetic mechanism is not always applicable to other NMDs. Third, our study had a diagnostic limitation of only single recording of Holter ECG for NSVT.…”
Section: Limitationmentioning
confidence: 99%
“…DM1 is the most common adult form of muscular dystrophy with a prevalence of 1 in 8000, characterized by progressive muscle weakness and atrophy, myotonia, early-onset cataracts and multiple organ involvement [4, 5]. The cardiac conduction system is selectively involved in DM1, and severe cardiac arrhythmias and respiratory insufficiency are the most frequent causes of death in these patients [6].…”
Section: Introductionmentioning
confidence: 99%